Advances in the diagnosis of acute pancreatitis. Issue 1002 (5th May 2009) - Rickes, S; Uhle, C
Abstract : Early and accurate assessment of both the aetiology and the severity of acute pancreatitis enables clinicians to follow therapeutic algorithms and can result in better outcomes. Technological advances over the past decade, in particular the development of imaging modalities, have revolutionised the management of patients with acute pancreatitis. This article reviews approaches to determining the diagnosis, aetiology and severity of acute pancreatitis, with particular emphasis on new imaging techniques.